PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN OPPO SMARTPHONE - Nugraha Windusara, Dewa Bagus; Artha Kusuma, A.A. Gd Agung (E-Jurnal Manajemen; Vol 4 No 12 (2015), 2015)
Mobile phone is the development of a home phone that can be taken anywhere, because it is a mobile phone and also can help human activities not only to make calls but can send sms/ message, internet, listening to music, and even perpetuate human activities with camera technology. In order to study this study seek to influence the promotion mix (promotional mix) through simultaneous and partially on the Oppo smartphone purchase decision through the sampling technique used is Non-Probability Sampling. Smartphone Oppo Denpasar Teuku Umar appointed as research sites by making the vulnerable age of 16 years and over 100 people in the sample. multiple linear regression analysis showed direct, simultaneous and partial impact on the promotion mix Oppo smartphone purchase decision.
Keywords: promotion, promotion mix, purchasing decisions